Determinants of Actual Usage of Computer among Mathematics, Science and English Language Teachers in Secondary Schools in Selangor, Malaysia - D’silva, Jeffrey Lawrence (2007)
As we are heading towards achieving the goal of Vision 2020, numerous changes have been implemented in the system of education. Among them would be the paradigm shift from the traditional mode of teaching to one that is of the information technology based especially among the Mathematics, Science and English language (MSE) teachers. Numerous incentives were given to the MSE teachers to use the computer in schools but preliminary observations found that they are not fully utilizing these facilities. The aim of this study is to identify factors influencing the actual usage of computer (AUC) among secondary school MSE teachers. The factors investigated were attitude, perceived usefulness, perceived ease of use, computer self-efficacy, job relevance, computer compatibility, subjective norm and teachers’ demography. A self-administered survey questionnaire was sent to MSE secondary school teachers in 65 schools in the district of Petaling, in Selangor. Out of the 358 questionnaires, a total of 318 (88.9%) valid responses were used. The data collected were analyzed using exploratory data analysis, statistical descriptive and inferential statistics (t-test, One-way ANOVA, Pearson correlation, and multiple regression) using the SPSS. Overall, the study found that the AUC among MSE secondary school teachers were at the moderate level. Meanwhile, the socio-demographic factors of main subjects taught and training in computer usage showed significant differences in means of AUC. Besides, the constructs of attitude, perceived usefulness, perceived ease of use, job relevance, and computer compatibility showed significant positive relationship with AUC. The study too identified the best-fit model using the step-wise multiple regression and the best model explained 54.5% of variance in AUC. The most significant predictors of AUC were perceived ease of use, followed by perceived usefulness, job relevance, computer compatibility, and attitude. It is recommended that for MSE teachers to enhance on their level of AUC would need a concrete effort from the policy makers, school administrators, and teachers themselves. Future research is recommended to encompass a wider scope of constructs pertaining to AUC that incorporate among others financial incentives and type of school.